2022
DOI: 10.2147/jir.s357144
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Validation of a Prognostic Classifier Based on Lipid Metabolism-Related Genes for Breast Cancer

Abstract: Background The changes of lipid metabolism have been implicated in the development of many tumors, but its role in breast invasive carcinoma (BRCA) remains to be fully established. Here, we attempted to ascertain the prognostic value of lipid metabolism-related genes in BRCA. Methods We obtained RNA expression data and clinical information for BRCA and normal samples from public databases and downloaded a lipid metabolism-related gene set. Ingenuity Pathway Analysis (IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…This suggests that AP2S1 is involved in the lipoprotein metabolism and AP2S1 is linked with CPT1A. SORBS1 has been shown to be involved in the lipid metabolism [44,45] and other studies have proven that SORBS1 is associated with obesity and insulin signaling [46]. In addition, it has been shown that SORBS1 is a candidate gene that affects fatty acid traits in milk [47], thus we presume that it may affect the fatty acid composition of goat meat in IMF deposition.…”
Section: Discussionmentioning
confidence: 71%
“…This suggests that AP2S1 is involved in the lipoprotein metabolism and AP2S1 is linked with CPT1A. SORBS1 has been shown to be involved in the lipid metabolism [44,45] and other studies have proven that SORBS1 is associated with obesity and insulin signaling [46]. In addition, it has been shown that SORBS1 is a candidate gene that affects fatty acid traits in milk [47], thus we presume that it may affect the fatty acid composition of goat meat in IMF deposition.…”
Section: Discussionmentioning
confidence: 71%
“…ROC analysis confirmed the diagnostic utility of SORBS1 in patients with BRCA with high confidence scores. Similarly, many previous studies have demonstrated the importance of SORBS1 as a possible prognostic predictor in patients with various solid malignancies such as metastatic prostate [ 22 ], cervical [ 23 ] and breast cancers [ 24 ]. We performed KEGG analysis of SORBS1-correlated genes using TCGA data and found that the PI3K/AKT signaling pathway was the most significantly enriched signaling pathway.…”
Section: Discussionmentioning
confidence: 91%